In Vitro Determination of Antimicrobial, Antioxidant and Antiviral Properties of Greek Plant Extracts - Aliki Tsakni; Eirini Kyriakopoulou; Sophia Letsiou; Panagiotis Halvatsiotis; Haralambos Rigopoulos; Niki Vassilaki; Dimitra Houhoula (Microorganisms)
The medicinal potential of plant extracts, especially their antimicrobial, antioxidant, antiviral and cytotoxic properties, has gained significant attention in recent years. This study examined the in vitro bioactivities of several selected Greek medicinal plants, like Eucalyptus globulus L., Thymus vulgaris L., Salvia rosmarinus L. and Ocimum basilicum L., are well-known for their traditional therapeutic use. Minimum inhibitory concentration (MIC) assays were used to evaluate the antimicrobial activity of the extracts against pathogenic bacteria. The antioxidant activity was carried out using the DPPH method, while the cytotoxicity of the plants was determined using the Alamar Blue method. In addition, the antiviral efficacy of the samples was tested against DENV in different cell lines. The majority of medicinal herbs demonstrated significant antimicrobial action (MIC = 30–3000 μg∙mL−1). The extracts showed great antioxidant activity, while the Salvia rosmarinus L. extract turned out to be the most effective (IC50 = 12.89 ± 0.11 μg∙mL−1). In contrast, the extract of Eucalyptus globulus L. had the lowest antioxidant action (IC50 = 71.02 ± 0.42 μg∙mL−1). The results of the Alamar Blue method were presented with CC50 values, and it was shown that Eucalyptus globulus L. extract exhibited the highest cytotoxicity (CC50 = 5.94% v/v ± 0.04). Similarly, the results of the antiviral potential of extracts were expressed as EC50 values, and Eucalyptus globulus L. was characterized as the most effective sample against dengue virus infection, with EC50 values estimated at 2.37% v/v ± 0.6 (HuhD-2 cells infected with DENV-2) and 0.36% v/v ± 0.004 (Huh7.5 cells infected with DVR2A). These findings provide a foundation for further studies in order to combat infectious diseases and promote human health.